Rational Improvement of Molar Absorptivity Guided by Oscillator Strength: A Case Study with Furoindolizine‐Based Core Skeleton. Issue 52 (13th November 2015) - Lee, Youngjun; Jo, Ala; Park, Seung Bum
Abstract: The rational improvement of photophysical properties can be highly valuable for the discovery of novel organic fluorophores. Using our new design strategy guided by the oscillator strength, we developed a series of full‐color‐tunable furoindolizine analogs with improved molar absorptivity through the fusion of a furan ring into the indolizine‐based Seoul fluorophore. The excellent correlation between the computable values (oscillator strength and theoretical S0 –S1 energy gap) and photophysical properties (molar absorptivity and emission wavelength) confirmed the effectualness of our design strategy. Abstract : Molar absorptivity : Using a rational design strategy guided by the oscillator strength, a furo[3, 2‐ e ]indolizine‐based fluorescent core skeleton with an improved molar absorptivity was synthesized. A furan ring was fused into an indolizine‐based Seoul‐Fluor to demonstrate the predictablity of their photophysical properties.